The Virtual Dental Center: A Resource for Research and Education on the WWW - Palombo, Cláudio Roberto (1998)
The Virtual Dental Center is a scientific and educational environment, which uses the WWW paradigm, with the objective of facilitating information interchange among dentists throughout the world.